2020
DOI: 10.1177/0735633120923772
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Learning Technology Acceptance Model of WeChat by Adding New Psychological Constructs

Abstract: The extended constructs of technology acceptance model (TAM) have rarely been linked to psychological influence factors. This study complements for the missing link in literature through structural equation modeling and a nonparametric Mann–Whitney U test based on the data obtained from a large-scale questionnaire survey. It is concluded that (a) conformity behavior can be integrated into the TAM to establish a fit model in WeChat use in language learning at the significance level .05, (b) self-esteem can be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 32 publications
2
39
1
Order By: Relevance
“…The three psychological constructs indirectly and positively affected BICE through PUV, tasks, MSE, IM, PEU, and PU. The role of the three action-oriented psychological constructs should not be neglected in the context of foreign language learning (Khany & Amiri, 2018), and these results may contribute to the literature on the extended versions of the TAM (Yu, 2020). In addition, this study incorporated IM for language learning into the extended TAM, whereas other studies have incorporated IM as enjoyment into the extended TAM (Fagan et al, 2008;Sun & Gao, 2019).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The three psychological constructs indirectly and positively affected BICE through PUV, tasks, MSE, IM, PEU, and PU. The role of the three action-oriented psychological constructs should not be neglected in the context of foreign language learning (Khany & Amiri, 2018), and these results may contribute to the literature on the extended versions of the TAM (Yu, 2020). In addition, this study incorporated IM for language learning into the extended TAM, whereas other studies have incorporated IM as enjoyment into the extended TAM (Fagan et al, 2008;Sun & Gao, 2019).…”
Section: Discussionmentioning
confidence: 84%
“…In a theoretical review study, Kemp et al (2019) identified seven taxonomic groups of factors affecting the acceptance of educational technology in higher education: attitude, affect and motivation, social factors, usefulness and visibility, instructional attributes, perceived behavioural control, cognitive engagement, and system attributes. However, psychological constructs and intrinsic motivation for language learning, which may affect learners' acceptance of MALL, have rarely been incorporated into the extended versions of the TAM (Chen, 2018;Hoi, 2020;Nie et al, 2020;Yu, 2020). Therefore, this study extended the TAM by incorporating psychological constructs and intrinsic motivation for language learning to create a theoretical framework that can predict factors that affect learners' behavioural intention to continue engaging in MALL.…”
Section: Practitioner Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this aim, the research question guides this study is What antecedent factors impact students' intention to participate in elearning during the COVID-19 quarantine? To answer the stated research question, we develop an integrated theoretical model that encompasses several antecedent factors (perceived challenges during COVID-19, school and teachers' perceived preparedness) and constructs from Technology Acceptance Model (TAM: Davis, 1989), perceived usefulness and perceived ease of use (Yu, 2020). We conduct empirical research and collect data through an online survey questionnaire, focusing on university students as the target group.…”
Section: Introductionmentioning
confidence: 99%
“…DeLone & McLean, 1992, 2003DeLone, 1988). E-learning effectiveness is related to the acceptance (Yu, 2020a;Yu, 2020b) and frequent use of platforms at a post acceptance stage (DeLone & McLean, 1992). DeLone & McLean (1992) measured six dimensions of e-learning effectiveness: technology quality, information quality, technology use, learner satisfaction, individual impact, and organizational impact.…”
Section: Literature Reviewmentioning
confidence: 99%